An Overview of Flavonoids and Antioxidant Potential of Prosopis cineraria - Abha Chaudhary; Dharminder Sharma; Sandeep Kumar (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
Herbal medicines are becoming more and more significant in pharmaceutical treatments and healthcare systems. Herbal medicines and nutritious foods frequently have fewer adverse reactions than synthetic medications. Since the chemical components of plants are involved in the physiological processes of live flora, it is thought that these components are more suited to human physiology. One such valuable plant, Prosopis cineraria, commonly referred to as Khejri or Janti, is an indigenous plant found in dry regions of India. Ayurveda mentions this plant with several therapeutic advantages. The plant yields a variety of secondary metabolites, such as alkaloids, flavonoids, polyphenols, tannins, saponins, and resins. The components of Prosopis leaves and stem bark have several therapeutic benefits and can be used to treat a wide range of illnesses. Its dry pods aid in avoiding blood iron and calcium deficiencies as well as malnutrition from protein and calories. This book chapter provides insight into the flavonoids present in the different parts of the plant as well as the antioxidant activity described in earlier reports.